Study of the Effect of Procedural Justice on Performance - Rahma, Aulia; Tjahjono, Heru Kurnianto; Rahayu, Meika Kurnia Puji (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper aims to identify research trends on procedural justice on performance globally. The method used in this study is qualitative research with a bibliometric analysis. As for the data found, 122 documents were obtained and analyzed from 2014-2023. This dataset was converted to CSV format and for Bibliometrix in the analysis using VOSviewer. The study included publication distribution year, country, keywords, and authors. The findings of this research showed that the research trend from 2014 to 2023 Experienced a significant increase in interest and research related to procedural justice on performance. The United States is the country that contributes the most research publications, research trends show an increasing focus throughout this decade. The increasing focus on procedural justice on performance reflects a paradigm shift in understanding and dealing with the challenges and opportunities faced by organizations in applying the principles of procedural justice used in organizations to their employees. The main limitation of this study should be considered - the use of data derived only from the Scopus database. This paper reveals research trends and areas of procedural justice on performance over the past few years. The results can help organisations to quickly understand procedural justice in performance research. This paper also provides an alternative approach in conducting literature reviews with qualitative research analysis tools that were previously widely adopted in various disciplines and are relatively new compared to conventional systematic literature